Crossbreeding strategy evaluation between Boer and Indonesian goat based on pre-weaning traits - Widyas, N.; Nugroho, T.; Ratriyanto, A.; Prastowo, S. (International Journal of Agricultural Technology, 2021)
The livestock industry in Indonesia is dominated by smallholder farmers. Crossbreeding between local and exotic breeds is a common practice by these farmers in order to improve productivity. This study is evaluated the crossbreeding strategy between Boer goat and Jawarandu goats by observing the pre-weaning traits. In total of 3,815 records were obtained from the kids born between 2012–2015. The recorded data of offspring from three mating scenarios: B×B (Boer and Boer), B×J (Boer and Jawarandu), and B×(B×J) (Boer bucks and B×J does) were investigated. The birth weight (BW), weaning weight (WW), and average daily gain (ADG) were analysed. For all traits, B×B kids were compared to the other sub-populations. Genetic parameters for each trait were estimated using univariate animal models and solved via average information restricted maximum likelihood (AI-REML) procedures. The heritability of BW were 0.38±0.12, 0.41±0.0 and 0.12±0.07, respectively, and weaning weights were 0.12±0.07, 0.24±0.07 and 0.08±0.06, respectively. The heritability for ADG were 0.13±0.07, 0.14±0.05, and 0.06±0.05 for B×B, B×J, and B×(B×J) sub-populations, respectively. Genetic correlations among pre-weaning traits were generally high (>70%), while the phenotypic correlations were low to moderate. A crossbreeding system in which the two parental breeds were maximally differed as the best scenario. It produced higher additive genetic variability, corresponding to the higher chance of improvement through between-breed selection on pre-weaning traits.